REFERENSI COVER MAJALAH TEMPO EDISI 14 SEPTEMBER: KARIKATUR WAJAH JOKOWI DENGAN BAYANGAN HIDUNG PANJANG – JANJI TINGGAL JANJI - Marlia Marlia (Jurnal Semantik, 2020)
The objective of this study is to identify and describe the respondent's reference to the cover of Tempo: The 2019 September 14th edition of the appointment. Data is obtained from respondents through google forms shared via WhatsApp chat that is examined using the triangle of Odgen & Richards and truth table Keith Allan. Number of respondents 130 people. According to the three meanings of Odgen & Richards, it is considered a liar because it is reference to Pinokio which has the concept of a long nose-like wooden doll that is lying. Moreover, it is considered as an important appointment because it is reference to the appointment of a promise that has a concept of attitude that does not keep the promise. While based on truth table Keith Allan, a liar is a proposition false (F) because the first proposition (P) is the proposition False (F) and the second proposition (Q) is the proposition True (T) so that the straightness of the proposition can be concluded is a false proposition (F). It can be concluded that the pairing of the same with Pinocchio and the promise of appointment is not something absolute and identical with the lies.